Risk minimisation: the failure of electricity intra-day forward contracts. (2017) - Boroumand, Raphaël Homayoun; Goutte, Stéphane; Porcher, Simon; Porcher, Thomas
As market intermediaries, electricity retailers purchase electricity from the wholesale market or self-generate to 'deliver' to their customers. However, electricity retailers are uncertain about how much electricity their residential customers will use at any moment of the day until the customers actually turn on their switches. While demand uncertainty is a common feature of all commodity markets, retailers generally rely on storage to manage it. Individually, electricity retailers are exposed to joint volumetric and price risk on an hourly basis given the physical attributes of electricity. In the literature on electricity markets, few articles compare the efficiency of forward contracts, options and physical assets (i.e., power plants) within intra-day hourly hedging portfolios, while electricity markets are precisely hourly markets. We analyse portfolios composed of forward contracts and/or power plants for specific hourly clusters based on electricity market data from 2013 to 2015 from the integrated German-Austrian spot market. Using a VaR and CVaR model, we prove that intra-day hedging with forward contracts is structurally inefficient compared to financial options and physical assets, no matter the cluster hour.